2010
DOI: 10.1111/j.1553-2712.2010.00960.x
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Pediatric Gastroenteritis: A Comparative Analysis of Pediatric Emergency Physicians’ Practice Patterns

Abstract: Objectives: Acute gastroenteritis is a very common emergency department (ED) diagnosis accounting for greater than 1.5 million outpatient visits and 200,000 hospitalizations annually among children in the United States. Although guidelines exist to assist clinicians, they do not clearly address topics for which evidence is new or limited, including the use of antiemetic agents, probiotics, and intravenous (IV) fluid rehydration regimens. This study sought to describe the ED treatments administered to children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 34 publications
0
46
0
6
Order By: Relevance
“…In this study we have addressed the hypothesis that rotavirus infection triggers the release antagonists, but no etiology is done 90 .…”
Section: Results and Discussion Of The Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we have addressed the hypothesis that rotavirus infection triggers the release antagonists, but no etiology is done 90 .…”
Section: Results and Discussion Of The Papersmentioning
confidence: 99%
“…A future alternative treatment strategy can be to prevent dehydration by reducing vomiting through use of 5--HT 3 receptor antagonists. In the US and Canada 5--HT 3 receptor antagonist are already used to treat vomiting in children with acute gastroenteritis, although no etiology is done 90 .…”
Section: Treatment and Preventionmentioning
confidence: 99%
“…A recent analysis of practice patterns revealed that 67% of U.S. pediatric emergency physicians routinely administer antiemetics to toddlers and young children, with ondansetron as the agent of choice of those responding. 46 Ondansetron was 1 of the 10 most frequently prescribed drugs in children 2 to 17 years of age: fifth most common in 2 to 4 year olds (19 occurrences per 100 hospitalizations), second most common in 5 to 11 year olds (30 occurrences per 100 hospitalizations), and most common in 12 to 17 year olds (30 occurrences per 100 hospitalizations). 47 Use in this condition is despite the fact that published guidelines do not recommend routine administration.…”
Section: Discussionmentioning
confidence: 99%
“…There is significant evidence that ondansetron is associated with a much lower rate of side-effects than other antiemetics and that it decreases the risk of persistent vomiting, the use of intravenous fluids, and hospital admission in children [44 ,45]. One study that evaluated current gastroenteritis therapies by pediatric emergency care providers in the United States and Canada found that ondansetron is routinely administered for mild-to-moderate dehydration with persistent vomiting in patients who failed oral rehydration attempts [46 ]. DeCamp et al [47] published a recent meta-analysis that reviewed six ondansetron-based studies over the past decade.…”
Section: Use Of Antiemetics With Rapid Fluid Resuscitationmentioning
confidence: 98%